Elaboración del estudio de prefactibilidad para el montaje de una empresa productora de paneles divisorios interiores a partir de cartón reciclado en la ciudad de Bogotá D.C. (2017)
This document includes the description of the pre-feasibility study for the Assembly of a company producing internal partition panels made from recycled cardboard.